Survey analysis for Indigenous policy in Australia : social science perspectives - Hunter, B. H. (Boyd H.); Biddle, Nicholas, Dr (Research monograph (Australian National University. Centre for Aboriginal Economic Policy Research), 2012)
This monograph presents the refereed, and peer-reviewed, edited proceedings of a conference organised by Centre for Aboriginal Economic Policy Research (CAEPR) and the Australian Bureau of Statistics (ABS): 'Social Science Perspectives on the 2008 National Aboriginal and Torres Strait Islander Social Survey'. The conference was held in Haydon Allen Tank at The Australian National University (ANU) in Canberra over two days on Monday 11 and Tuesday 12 April 2011.